HBQ-India: an uncommon hemoglobin variant - Dhawle, Manjusha; Methwani, Ashok; Tangde, Ashwini; Bindu, Rajan (International Journal of Research in Medical Sciences, 2018)
Background: HbQ-India is a rare alpha chain variant. It is an important member of the hemoglobin Q family molecularly characterized by replacement of aspartic acid by histidine. It usually presents in the heterozygous state. It becomes symptomatic only in the homozygous state and when present in association with other conditions like beta-thalassaemia, alpha thalassaemia, HbE and HbH. The Sindhi is one of the largest linguistic communities, migrated about 65 years back from the Sindh province of west Pakistan to India. They are a high-risk community for beta thalassaemia gene in India with a carrier frequency ranging from 5 to 12 % with a distinct regional variability. Methods: A total 343 cases were screened for hemoglobinopathies in Sindhi population. Detail history was taken from each patient and pertinent physical finding were noted. CBC, Peripheral smear and HPLC were performed. During screening we observed that few samples showed an unknown peak at a retention time of 4.7 min on HPLC and comparison with reference chromatograms indicated them to be HbQ India and it is confirmed by amplification restriction mutation system polymerase chain reaction (ARMS-PCR). Results: We found 13 cases, 12 cases of HbQ India and 1 case of HbQ-beta thalassaemia in Sindhi population of Aurangabad in Maharashtra. Conclusions: India is known as a country with a high prevalence of different types of hemoglobinopathy. Now a days HPLC, IEF, ARMS-PCR, DNA sequencing are the methods available for the diagnosis of the abnormal Hb like HbQ-lndia. HPLC is a cheaper alternative to ARMS-PCR in the detection of rare hemoglobinopathies.